Entomopathogenic Fungi from South Sumatra (Indonesia) Pathogenicity to Egg, Larvae, and Adult of Aedes aegypti - Indri Ramayanti; Siti Herlinda; Ahmad Muslim; Hamzah Hasyim (HAYATI Journal of Biosciences, 2023)
Fungi from South Sumatra (Indonesia) were identified morphologically and molecularly, and their pathogenicity to egg, larvae, and adult Aedes aegypti was evaluated. The fungal isolates used for bioassay were 11 isolates from this study and 4 isolates from the laboratory collection. Fifteen isolates of five fungal species (Metarhizium anisopliae, Penicillium citrinum, Talaromyces diversus, Beauveria bassiana, and Purpureocillium lilacinum) from South Sumatra, Indonesia, were pathogenic to the egg, larvae, and adult of Ae. aegypti. Egg mortality caused by M. anisopliae isolate MSwTp3 was the highest (38.31%). A novel finding of this study was that the eggs exposed to the fungus not only killed the eggs but could continue to kill the emerging larvae, pupae, and adults. The five fungal species induced larval mortality between 52.22−94.44% and adult mortality between 50.00−92.22%. Fungal strains belonging to M. anisopliae, P. citrinum, T. diversus, and B. bassiana from South Sumatra seem to possess remarkable ovicidal, larvicidal and adulticidal activity against Ae. aegypti. M. anisopliae, P. citrinum, T. diversus, and B. bassiana had the potential as entomopathogens to be developed into ovicides, larvicides, and adulticides for controlling Ae. aegypti.